Currency wars not public debt may create a financial meltdown - Robin Pope; Reinhard Selten (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In studies concluding that public debt may hamper GDP growth, the debt tipping effects are estimated as if there were a single global currency. This means that such studies ignore the likely biggest cause of changes in growth rates, namely damage from exchange rate liquidity shocks because we do not live in the fairyland of a single global currency. The conclusions of these studies are accordingly invalid. They deflect attention from a prime danger, namely an exchange-rate-precipitated global meltdown a danger of the repetition of events of 80 years ago. These studies are misleading in other respects too. Their estimates of growth determinants conflate the differential growth effects of government expenditures with those of tax concessions and uncollected taxes as contributors to government debt. The conflation entices adherents to see all increases in government debt as arising from excessive expenditures, so that in the current crisis, the real problems are unaddressed. Instead, harmful policies of austerity and depreciation, are proposed that would exacerbate the problems and heighten the dangers. In this global downturn, policy should be redirected to avoid repeating the tragedies of the 1930s and 1940s when armaments, Hitler, a world war, then a Korean war were all needed to make the fiscal stimulus mighty enough to restore US employment after the 1930s global meltdown from exchange rate liquidity shocks. Needed are employment-generating fiscal stimulus in societally productive activities, reinstatement of the constraints that countries employed into the 1970s to limit government interest rates, and moves to instate a single global currency. JEL: E6, F31, G01, H62, H63
Keywords: G01; H62; F31; 330